Analisis Saluran Pemasaran Buah Naga Super Merah pada Kelompok Tani Karya Peni Kabupaten Banyuwangi - Wardani, Citra Yunia; Budiasa, I Wayan; Artini, Ni Wayan Putu (Nandur; Vol 1 No 1 (2020), 2020)
Abstrak